Drug delivery and anticancer activity of biosynthesised mesoporous Fe2O3 nanoparticles - Firoozeh Abolhasani Zadeh; Saade Abdalkareem Jasim; Nigora E. Atakhanova; Hasan Sh. Majdi; Mohammed Abed Jawad; Mohammed Khudair Hasan; Fariba Borhani; Mehrdad Khatami (IET Nanobiotechnology)
Abstract Mesoporous magnetic nanoparticles of haematite were synthesised using plant extracts according to bioethics principles. The structural, physical and chemical properties of mesoporous Fe2O3 nanoparticles synthesised with the green chemistry approach were evaluated by XRD, SEM, EDAX, BET, VSM and HRTEM analysis. Then, their toxicity against normal HUVECs and MCF7 cancer cells was evaluated by MTT assay for 48 h. These biogenic mesoporous magnetic nanoparticles have over 71% of doxorubicin loading efficiency, resulting in a 50% reduction of cancer cells at a 0.5 μg.ml−1 concentration. Therefore, it is suggested that mesoporous magnetic nanoparticles be used as a multifunctional agent in medicine (therapeutic‐diagnostic). The produced mesoporous magnetic nanoparticles with its inherent structural properties such as polygonal structure (increasing surface area to particle volume) and porosity with large pore volume became a suitable substrate for loading the anti‐cancer drug doxorubicin.